Parashurama - incarnation of Vishnu depicted with an axe - 039 - Saurabh Saxena (2022)
Image courtesy : Saurabh Saxena - https://puratattva.in/ The deity here could be Parashurama, since his weapon is an axe. Him being an incarnation of Vishnu, the deity is also shown with conch and discus.